Cardiovascular and Metabolic Risk in Women in the First Year Postpartum: Allostatic Load as a Function of Race, Ethnicity and Poverty Status - Shalowitz, Madeleine U. (Am J Perinatol, 2018)
OBJECTIVE: Allostatic load (AL) represents multi-system physiological “wear-and-tear” reflecting emerging chronic disease risk. We assessed AL during the first year postpartum in a diverse community sample with known health disparities. METHODS: The Eunice Kennedy Shriver National Institute for Child Health and Human Development Community Child Health Network enrolled 2,448 predominantly low income African-American, Latina and White women immediately after delivery of liveborn infants at ≥ weeks gestation, following them over time with interviews, clinical measures, and biomarkers. AL at six and twelve months postpartum was measured by body mass index, waist:hip ratio, blood pressure, pulse, hgbAlC, hsCRP, total cholesterol and HDL, and diurnal cortisol slope. RESULTS: Adverse AL health-risk profiles were significantly more prevalent among African-American women compared to non-Hispanic Whites, with Latinas intermediate. Breastfeeding was protective, particularly for White women. Complications of pregnancy were associated with higher AL, and disparities persisted or worsened through the first year postpartum. CONCLUSIONS: Adverse AL profiles occurred in a substantial proportion of postpartum women, and disparities did not improve from birth to one year. Breastfeeding was protective for the mother.